Phenazine derivatives for optical sensing: a review. Issue 33 (11th August 2020) - Xiao-Ni, Qi; Dang, Li-Rong; Qu, Wen-Jun; Zhang, You-Ming; Yao, Hong; Lin, Qi; Wei, Tai-Bao
Abstract : Phenazine exhibiting an electron-deficient skeleton, lone pair of electrons on nitrogen atoms, and other properties (such as tunable structures, excellent optical performance and proper binding abilities) can effectively sense target ions or molecules via non-covalent interactions, involving hydrogen bonds, anion–π interactions, metal coordination and other weak forces. Abstract : Phenazine exhibiting an electron-deficient skeleton, lone pair of electrons on nitrogen atoms, and other properties (such as tunable structures, excellent optical performance and proper binding abilities) can effectively sense target ions or molecules via non-covalent interactions, involving hydrogen bonds, anion–π interactions, metal coordination and other weak forces. These distinct characteristics enable phenazine derivatives to be available in variety of sensors, which have already been demonstrated successfully in the field of sensing. More importantly, phenazine derivatives can be potentially applied in biosensors. Therefore, the latest progress related to the application of phenazine derivatives in optical sensing is summarized. It is expected that phenazine derivatives will garner much interest in the fabrication of sensors and bio sensing applications in the near future.